Journal of Forensic Medicine & Toxicology, April-June 2020, Vol. 14, No. 2 1633 The Impact of High Cortisol Level in Increasing Incidence of Infection Cases among Acute Stroke Patients - Indah Ari Handaayani1, Joseph Eko Wahono Rahardjo1, Muhammad Hamdan1, Paulus Sugianto1, Achmad Firda (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Infection in the stroke was a treatment major problem, because it determines the prognosis. In the acute phase of stroke, high level cortisol may lead to a decreased immune system and patients tend to be more susceptible to infection. The correlation of serum cortisol level among acute stroke patients with incidence of infection was not fully investigated. Objective: The aim of this study was to determine the relationship between initial serum cortisol levels and the incidence of infection in acute stroke patients. Method: A prospective cohort study was conducted on 32 of acute stroke patients who admitted in RSUD Dr. Soetomo Surabaya during the period December 2015 to February 2016. Total of 2 cc to the venous blood within 48 hours in onset of stroke being examined of serum cortisol. During the 7 days of hospitalization, the patient was observed for signs of infection, both clinically and the investigation in accordance with the operational definition. Results: In the infected group there were 8 people (50%) with high cortisol levels (p = 0.015; RR 15,000; 95% IK 1.583-143,171); 6 people were (50%) using urine catheter (p = 0.049; RR 6,667; 95% IK 1.067-30.085); And 6 people were (54.5%) using NGT (p = 0,035; RR 7,200; 95% IK 1.311 - 39,557). In multivariate analysis obtained that Odds Ratio (OR) 15,468 based on high cortisol and OR 7,469 based on NGT usage. Conclusion: High cortisol levels and the use of NGT had the effect on the incidence of infection in acute stroke